Assessing role of water user associations in enhancing efficiency of rice (Oryza sativa) production: Insights from the Nagarjuna Sagar Project command area of Andhra Pradesh - M, BALASUBRAMANIAN; NITHYASHREE, M L; P, VENKATESH; SINGH, D R; M, UMAMAGESWARI (The Indian Journal of Agricultural Sciences, 2025)
Addressing the rice (Oryza sativa L.) yield gap is one of the most necessary steps in sustaining food security. The survey was carried out during 2021–22 to investigate the sources of technical efficiency in rice farming within the Nagarjuna Sagar Project Command area (NSP) of Andhra Pradesh, India. Utilizing Data Envelopment Analysis (DEA) with a double bootstrap approach, the study analysed the primary data collected from 112 Water User Association (WUA) participants and 86 non-participants across the Kanapparu, Muppalla, and Nadenla villages in Muppalla, and Nadenla blocks of the NSP command area of Guntur district. The estimates of average technical efficiency (TE) of 0.69 indicated that farming households can reduce inputs by 31% without altering output levels. Key factors influencing technical efficiency were obtained by double bootstrap estimation revealing participation in Water User Associations (WUAs) enhances the technical efficiency of rice farming. Fixation of water charges and the equitable distribution of irrigation water were found to be key factors associated with the higher level of participation in WUA.